(untitled) (Scientific journal of the Fergana State University, 2026)
The study of non-traditional language learning methods has gained significant attention in recent years due to their potential to enhance cognitive engagement and improve language acquisition outcomes. This article examines the role of non-traditional methods, such as immersive learning, gamification, and context-based teaching, in fostering language learning and their impact on brain activity. Findings suggest that non-traditional methods not only improve language retention but also stimulate critical areas of the brain associated with memory, problem-solving, and emotional engagement.